The Causal Effect of Board Size in the Performance of Closely Held Corporations - Morten Bennedsen; Hans Christian Kongsted; Kasper Meisner Nielsen (Copenhagen Business School (CBS), Department of Economics, 2007)
Boards are endogenously chosen institutions determined by observable and unobservable firm characteristics. Empirical studies of large publicly traded firms have successfully controlled for observable determinants of board size and shown a robust negative relationship between board size and firm performance. The evidence on smaller closely held firms is less clear; we argue that existing work has been incomplete in analyzing the causal relationship due to weak identification strategies. Using a rich data set of almost 6,000 small and medium-sized closely held corporations we provide a causal analysis of board size effects on firm performance using a novel instrument given by the number of children of the founders of the firms. First, we find no empirical evidence of adverse board size effects when the size of the board lies in the typical range for closely held corporations of three to six directors. Second, we find a significantly negative board size effect for the minority of closely held firms that are characterized by having comparatively large boards of seven or more members and non-complex operations.
hdl:10398/7600
Keywords: G10; 330